STRATEGI PSK DALAM MENGGUNAKAN MEDIA SOSIAL DI KOTA MANADO - Ratu, Melinda; Mamosey, Welly E.; Mawara, Jetty E. T. (HOLISTIK, Journal Of Social and Culture, 2020)
The development of information technology in Indonesia is very fast including the internet turned out to have a great impact on the whole life. The development of technology that makes many people use this technology to make buy and sell transactions. It is not strange considering the growing number of Internet users can be the potential to be entered by business people anywhere and anytime.Technology, the Internet, and prostitution are three things that are intertwined. Advances in communication and Internet technology allow one to quickly get to the information. Prostitution also does not blind technology and participates in the development of the era so that prostitution becomes increasingly diverse and sophisticated. These two apps are often used by the (prostituted online) Michat and also the Facebook.In finding customers using Facebook relies heavily on the Group Admins who act as pimp, Michat is very easy to find a customer because in search of friends or customers can use the location feature.A commercial Sex worker transaction place that uses social media in search of customers such as at boarding house and hotels. The development of technology in particular social media chats as one technology has influenced and then changed the interaction pattern between sex workers and prospective consumers.  The use of necessary media for prostitution is one of culture lag or cultural deterioration, because it makes use of technology is not as it should be. Sex workers who use social media have described social change in prostitution. Keywords: prostitute, application, social media